A novel rotation detection method based on the capacitance principle and triboelectric effect. (24th September 2021) - Wang, Zhihua; Li, Zixuan; Yao, Tao; Wang, Zhiying; Zhang, Huijuan
Abstract: With the rapid development of automation, more rotating monitoring equipment has been applied in modern industrial and civil fields. Conventional rotating monitoring sensors such as Hall rotating sensor and variable reluctance rotating sensor have a complex structure and their split structure is not convenient to layout. In the present study, a multi-layer structure rotation measurement sensor (MSRMS) is proposed based on the triboelectric effect and the capacitance principle. The proposed sensor consists of a stator and a rotor and measures the rotational speed based on the relative rotation between the copper electrode (Cu) on the stator and the polytetrafluoroethylene film on the rotor, and the variations of the electrostatic-induced voltage in the electrode, and can generate an alternating voltage waveform. When the rotor rotates, the correlation between the relative area of the stator and rotor electrode plates and the capacitor capacitance can be applied to measure the rotation angle. Then the MSRMS is applied to the programmable motor and the tripod for testing. It is found that the maximum error of the speed measurement is less than 0.2%. The coefficient of determination R 2 of the fitting for the distribution of the capacitance and the rotation angle is higher than 0.99688, which shows that capacitance is related to the rotation angle. The proposed sensor can not only measure the static rotation angle, but also dynamically monitor the speed and direction of rotation, and has a good application prospect.